A health promotion web application for virtual teacher training - Virginia Gugelmeier; María Del Carmen López Jordi; Alicia Gómez; Susana Cornejo (Universidad de la República, 2023)
The training of the staff in study centres is scarce around oral health, being the ICT valid tools to improve it. Objective: to design a web app for the immediate treatment of traumatic oral injuries in schoolchildren. Method: a virtual protocol about the immediate treatment given to children in the event of a traumatic dental injury was designed. The contents follow an instructional design with a logical order of appearance. Results: the app was planned together with ICT analysts, following the compatibility demands of browsers and information safety and the PHP-Laravel programming language was applied and the MySQL database engine. Discussion: The digital environment or educative spaces are the objects or gadgets of a digital nature in a concrete scenario, social and culturally built, with the purpose of favouring valuable learning experiences. Conclusions: a training app was created, promoting de usefulness of open educational resources for the oral health promotion.